Product Training for the Technical Expert: The Art of Developing and Delivering Hands-On Learning - Bixby, Daniel W (Wiley - IEEE, 2018)
"I was pleased to review Dan's new book - pleased because he addresses an old topic in a new way. He is making no assumptions for trainers who are not fully experienced and seasoned. He takes them step-by-step through practical and realistic methods to set up training graduates to actually be on-the-job performers. Enjoy, learn and be inspired." Jim Kirkpatrick, PhD, Senior Consultant, Kirkpatrick Partners, USA "Daniel Bixby's approach to product training for technical experts is practical, relevant and exactly what anyone who is required to train others on technical content really needs. He writes with candor and with a sense of ease, making the reader feel as though he is right there with you helping to develop your training competency. A must read for anyone on your team required to provide technical training to others!" Jennifer Alfaro, Chief Human Resources Officer, USA An expert guide to developing and delivering technical product training programs While there are many books on talent development, leadership training, and internal training program development, there are precious few offering subject matter experts' (SMEs) guidance on training others to get the most out of their products. Written by a training expert with many years of experience working at top technology companies, Product Training for the Technical Expert fills the gap in the training literature by providing technical experts with a comprehensive handbook on becoming effective product training instructors. When new technology is rapidly transformed into products for popular consumption, technical experts, such as engineers, and other subject matter experts, are the ones tasked with instructing the public on their use. Unfortunately, most of them have little or no prior experience or training in adult education and don't have a clue about how to transfer their knowledge to others. In this book, author Daniel W. Bixby draws upon his vast experience developing and delivering training programs at Honeywell, Telex, Bosch, TE Connectivity, and CommScope, among other technology companies, to arm SMEs with the knowledge and skills they need to add "Product Training Specialist" to their resumes. Addresses an area of training too often overlooked and ignored in the professional literature Equips SMEs with the tools they need to become effective product instructors Covers both the educational and business aspects of product training for SMEs Packed with tables, illustrations, problem-and-solution sets, tutorials, enlightening real-world examples, worksheets, and group or self-study questions Features a companion website with worksheets and other valuable tools: www.wiley.com/go/Bixby A must-have professional development resource for students and experienced technical experts alike Product Training for the Technical Expert is an ideal guide for engineers, product managers, product marketing managers, and technical instructors looking to expand their repertoires and hone their skills. It also makes an excellent course text for graduate-level engineering programs.